Psychology in society? Addressing the academic/activist divide and the “magical boundary” of the academy - Kiguwa, Peace (PINS-Psychology in Society, 2025)
“…we tell ourselves and our students that everything is simultaneously political and theoretical, yet we seem to have a hard time connecting the two outside the university” (Blomley, 1994: 28) “The country we want to live in”: Psychology in society A fairly recent South African text initiative titled The country we want to live in: Hate crimes and homophobia in the lives of black lesbian South Africans edited by gender and social activists Nonhlanhla Mkhize, Jane Bennett, Vasu Reddy and Relebohile Moletsane (2010) presents a stark and grim reminder that full and active citizenship in post-apartheid South Africa remains elusive for particular groups of people, living on the margins of society, whose lives remain unaffected by the much lauded constitutional gains and redress initiatives of a young democracy. Reflecting upon those haunting words: “the country we want to live in” incites me to ponder this country that we live in. I think about citizenship and belonging. I think about violence and its gendered forms. I think about feminist activism in South Africa and I think about my chosen profession, Psychology. What this title presents back to me is the promise of what a critical psychology project should be, must be. And so, I think reflectively not only about my rootedness in a profession that has historically strived to maintain a “magic boundary” between its intellectual, academic pursuits and broader society, but also about the different spaces and avenues that have critically and reflectively attempted to engage this dichotomy as a means of redress.